Carbapenem-Resistant Enterobacteriaceae Infections: Taiwan Aspects - Jean, Shio-Shin; Lee, Nan-Yao; Tang, Hung-Jen; Lu, Min-Chi; Ko, Wen-Chien; Hsueh, Po-Ren (Frontiers in Microbiology, 2018)
Carbapenem-resistant Enterobacteriaceae (CRE), a major resistance concern emerging during the last decade because of significantly compromising the efficacy of carbapenem agents, has currently become an important focus of infection control. Many investigations have shown a high association of CRE infections with high case-fatality rates. In Taiwan, a few surveys observed that a significant proportion (29% to 47%) of the CR-Klebsiella pneumoniae isolates harbored a plasmidic allele encoding K. pneumoniae carbapenemases (KPC, especially KPC-2). A significant increase in the number of oxacillinase (OXA)-48-like carbapenemases among CR-K. pneumoniae isolates was observed between 2012 and 2015. By striking contrast, isolates of CR-Escherichia coli and CR-Enterobacter species in Taiwan had a much lower percentage of carbapenemase production than CR-K. pneumoniae isolates. This differs from isolates found in China as well as in the India subcontinent. Apart from the hospital setting, CRE was also cultured from the inpatients from communities or long-term care facilities (LTCF). Therefore, implementation of regular CRE screening of LTCF residents, strict disinfectant use in nursing homes and hospital settings, and appropriate control of antibiotic prescriptions is suggested to alleviate the spread of clinical CRE isolates in Taiwan. Although there are some promising new antibiotics against CRE, such as ceftazidime-avibactam, meropenem-vaborbactam, aztreonam-avibactam and cefiderocol, these agents are not available in Taiwan currently. Therefore, in order to effectively decrease case-fatality rates among patients with the infections owing to carbapenemase-producing CRE isolates, combination antibiotic schemes, including colistin (or amikacin) and/or tigecycline in combination with an anti-pseudomonal carbapenem agent, remain the mainstay for treating clinical CRE infections.